Social and Non-Social Cognitive Enhancement in Cocaine Users—A Closer Look on Enhancement Motives for Cocaine Consumption - Kexel, Ann-Kathrin; Vonmoos, Matthias; Preller, Katrin H.; Hulka, Lea M.; Seifritz, Erich; Quednow, Boris B. (Frontiers in Psychiatry, 2020)
Background Cognitive disturbances of chronic cocaine users (CU) have been repeatedly investigated. However, it is yet unknown how CU using cocaine for cognitive or social enhancement differ from stimulant-naïve controls and CU that do not have these motives. More precisely, we assumed that CU with an enhancement motive self-medicate deficits in specific cognitive abilities, i.e., they use cocaine to enhance their performance in either social (social motive) or non-social cognitive situations (cognitive motive). Methods Forty-two CU were categorized according to their motives for cocaine consumption into social and non-social motive groups as well as cognitive and non-cognitive motive groups, respectively. Subsequently, CU motive groups were compared to 48 stimulant-naïve controls in their social and non-social cognitive functioning applying a comprehensive neuropsychological test battery. Results The social motive group showed deficits in cognitive empathy compared to controls (Cohen’s d = 0.65) and the non-social motive group (d = 0.60). No mentionable effects were found for emotional empathy and Theory-of-Mind. Cognitive and non-cognitive motive groups both showed general cognitive deficits but with different patterns of impairments compared to controls: the cognitive motive group had deficits mainly in working memory (d = 0.84) and declarative memory (d = 0.60), whereas the non-cognitive motive group also had deficits in working memory (d = 0.61) but additionally in executive functions (d = 0.67). For the domains declarative memory and executive functions, the respective other CU group displayed intermediate performance. Conclusions This study demonstrates that cocaine is partially instrumentalized by CU with specific enhancement motives to counteract related cognitive impairments.